The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.4102/sajpsychiatry.v22i1.836
|View full text |Cite
|
Sign up to set email alerts
|

The functioning and behaviour of biological parents of children diagnosed with attention-deficit/hyperactivity disorder, attending the outpatient department at Weskoppies Hospital, Pretoria

Abstract: BackgroundADHD (attention-deficit/hyperactivity disorder) is gradually being acknowledged as a functionally impairing disorder across the lifespan, underscored by heritability. Nonetheless, lack of ADHD (adult attention-deficit/hyperactivity disorder) data from South Africa is alarming which could be due to either the unawareness of ADHD symptoms or underutilisation of available screening measures. Undiagnosed ADHD may influence family- and working lives unpleasantly. Parenting a child with ADHD may intensify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…The flowchart in Figure 1 illustrates the process of screening and data extraction undertaken in the review. Overall, 18 studies [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] were identified to have reported on the prevalence of mental illness among parents of children receiving treatment in CAMHS.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The flowchart in Figure 1 illustrates the process of screening and data extraction undertaken in the review. Overall, 18 studies [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] were identified to have reported on the prevalence of mental illness among parents of children receiving treatment in CAMHS.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies had a focus on prevalence rates in relation to specific mental illnesses, either in the parent [40] (see Table 4) or the child [41][42][43] (see Table 5). Finally, some studies reported the number of parents with a specific mental illness who had children attending CAMHS with a specific mental illness [44][45][46][47][48][49] (see Table 6).…”
Section: Reported Prevalence Of Mental Illness Among Parents Of Children Attending Camhsmentioning
confidence: 99%
See 3 more Smart Citations